2020
DOI: 10.1186/s12902-020-00596-3
|View full text |Cite
|
Sign up to set email alerts
|

Leu72Met polymorphism of GHRL gene decreases susceptibility to type 2 diabetes mellitus in a Mexican population

Abstract: Background: Type 2 diabetes mellitus (T2D) is the most frequent type of diabetes. It has a multifactorial etiology, affecting millions of people worldwide. Ghrelin gene (GHRL) encodes the ghrelin peptide, which promotes food intake, induces body weight and adipogenesis. Several single nucleotide polymorphisms (SNPs) in GHRL gene have been associated with metabolic diseases. A protective effect of the Leu72Met (rs696217) polymorphism has been described for T2D in some populations, but this effect seems to depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…[ 51 52 ] The association of GHRL p.Leu72Met with insulin resistance and T2DM risk has remained controversial. [ 53 54 55 ] However, a positive association between GHRL p.Leu72Met and early onset of obesity was found amongst Italian obese children. [ 56 ] In our cohort, we have identified GHRL p.Leu72Met in five PCOS patients, of which three were obese and two subjects had normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 52 ] The association of GHRL p.Leu72Met with insulin resistance and T2DM risk has remained controversial. [ 53 54 55 ] However, a positive association between GHRL p.Leu72Met and early onset of obesity was found amongst Italian obese children. [ 56 ] In our cohort, we have identified GHRL p.Leu72Met in five PCOS patients, of which three were obese and two subjects had normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The genotypic and allelic frequencies of the genotypes of GHRL Leu72Met in our study were similar to those reported in a Mexican-American population of Los Angeles [ 33 ]. Nevertheless, Rivera-León et al observed different frequencies in a population of young adults from western Mexico with both normal weight and obesity; a possible explanation for this might be the use of different techniques to determine the genotypes [ 34 ]. Moreover, the allelic and genotypic frequencies of Gln223Arg genotypes of the LEPR gene were similar to those reported in the Mexican-American population of Los Angeles [ 35 ], as well as in young populations with normal weight and overweight in southern and western Mexico [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damaging variants in GYG1 (SLP = 3.22) cause deficiency of glycogenin 1, resulting in glycogen storage myopathies, but have not been reported to be associated with diabetes 33 . GHRL (SLP = −3.15) encodes the ghrelin‐obestatin preproprotein which is cleaved to yield two peptides, ghrelin and obestatin, which are involved in appetite and energy metabolism and there have been some studies which have claimed that the common Leu72Met (rs696217) variant is associated with reduced risk of T2D although the effect does not seem to be consistent and the gene was not highlighted in a large GWAS meta‐analysis 1,34 …”
Section: Discussionmentioning
confidence: 99%
“…33 GHRL (SLP = −3.15) encodes the ghrelin-obestatin preproprotein which is cleaved to yield two peptides, ghrelin and obestatin, which are involved in appetite and energy metabolism and there have been some studies which have claimed that the common Leu72Met (rs696217) variant is associated with reduced risk of T2D although the effect does not seem to be consistent and the gene was not highlighted in a large GWAS meta-analysis. 1,34 It is noteworthy that in the gene set analyses the second high- 12 of 14 -CURTIS function effects. 38 The fact that the frequency of LOF variants in INSR is similar in cases and controls, indicates that, although recessively acting variants can cause infantile hyperinsulinaemia followed by insulin dependent diabetes, the loss of function of a single copy of this gene has little discernible effect on risk of T2D.…”
Section: Curtismentioning
confidence: 99%